2012
DOI: 10.1104/pp.112.204420
|View full text |Cite
|
Sign up to set email alerts
|

Maize Source Leaf Adaptation to Nitrogen Deficiency Affects Not Only Nitrogen and Carbon Metabolism But Also Control of Phosphate Homeostasis    

Abstract: Crop plant development is strongly dependent on the availability of nitrogen (N) in the soil and the efficiency of N utilization for biomass production and yield. However, knowledge about molecular responses to N deprivation derives mainly from the study of model species. In this article, the metabolic adaptation of source leaves to low N was analyzed in maize (Zea mays) seedlings by parallel measurements of transcriptome and metabolome profiling. Inbred lines A188 and B73 were cultivated under sufficient (15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
170
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(200 citation statements)
references
References 97 publications
24
170
2
4
Order By: Relevance
“…Under N deficiency, many N transporters and proteins mediating N metabolism have differential expression or accumulation (Yang et al 2011;Liao et al 2012a;Schlüter et al 2012;Garnett et al 2013), although no specific genes mediating N uptake and assimilation were identified with differential expression in rice seedlings at the early stage of N limitation (Lian et al 2006). Here, we found eight genes regulating N assimilation with significant down-regulation at the transcriptional level in the ZD958 root after 12-day N deficiency (Fig.…”
Section: Differential Regulation Of Genes Mediating N Transport and Mmentioning
confidence: 69%
See 2 more Smart Citations
“…Under N deficiency, many N transporters and proteins mediating N metabolism have differential expression or accumulation (Yang et al 2011;Liao et al 2012a;Schlüter et al 2012;Garnett et al 2013), although no specific genes mediating N uptake and assimilation were identified with differential expression in rice seedlings at the early stage of N limitation (Lian et al 2006). Here, we found eight genes regulating N assimilation with significant down-regulation at the transcriptional level in the ZD958 root after 12-day N deficiency (Fig.…”
Section: Differential Regulation Of Genes Mediating N Transport and Mmentioning
confidence: 69%
“…Asparagine, featured by a high N/C ratio, serves as an efficient carrier for N transport (Miflin and Lea 1980); asparagine synthetase catalyzes synthesis of asparagine using glutamine as a substrate (Lam et al 1996). ASN2 expression is downregulated in maize source leaves under low N (Schlüter et al 2012). Down-regulation of ASN2 expression in ZD958 and other maize and teosinte roots ( Fig.…”
Section: Differential Regulation Of Genes Mediating N Transport and Mmentioning
confidence: 92%
See 1 more Smart Citation
“…N fertilizer supply has multiple direct and indirect effects on plant N metabolism (Stitt et al, 2002;Schlüter et al, 2012). In particular, it modifies the N content of newly produced leaves, leaf longevity/senescence, and the dynamics of light distribution inside expanding canopies (Evans, 1983(Evans, , 1989Moreau et al, 2012).…”
mentioning
confidence: 99%
“…Plants treated with NH 4 Cl, as exclusive nitrogen source, showed lower level of 388 Kaur and asthir: Sucrose and Glutamine Metabolism in Wheat Cereal Research Communications 44, 2016 total sugars than those treated with NO 3 -. The rapid assimilation of NH 4 + in glutamine led to a consumption of carbon skeletons, causing depletion of the foliar starch and sucrose (Ikram et al 2012;Schluter et al 2012), likewise Britto and Kronzucker (2002) concluded that the consumption of fixed carbon during the assimilation of NH 4 + could appreciably reduce sugars results in increases amino acids.…”
Section: Discussionmentioning
confidence: 99%